2021
DOI: 10.1261/rna.079008.121
|View full text |Cite
|
Sign up to set email alerts
|

Using quantitative reconstitution to investigate multicomponent condensates

Abstract: Many biomolecular condensates are thought to form via liquid-liquid phase separation (LLPS) of multivalent macromolecules. For those that form through this mechanism, our understanding has benefitted significantly from biochemical reconstitutions of key components and activities. Reconstitutions of RNA-based condensates to date have mostly been based on relatively simple collections of molecules. However, proteomics and sequencing data indicate that natural RNA-based condensates are enriched in hundreds to tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 109 publications
(160 reference statements)
1
19
0
Order By: Relevance
“…It is well-established that the dilute and concentrated phases of a LLPS system have different protein composition and concentrations (Currie and Rosen, 2022; Koga et al, 2011; Magdalena Estirado et al, 2020; Nott et al, 2015; Yewdall et al, 2021). The rate of fixation is known to vary with both factors by orders of magnitude, with the timescale of fixation ranging from seconds to hours (Hoffman et al, 2015; Kamps et al, 2019; Metz et al, 2006; Metz et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…It is well-established that the dilute and concentrated phases of a LLPS system have different protein composition and concentrations (Currie and Rosen, 2022; Koga et al, 2011; Magdalena Estirado et al, 2020; Nott et al, 2015; Yewdall et al, 2021). The rate of fixation is known to vary with both factors by orders of magnitude, with the timescale of fixation ranging from seconds to hours (Hoffman et al, 2015; Kamps et al, 2019; Metz et al, 2006; Metz et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…In this study we found that reconstituting P bodies in vitro with all of the highly-concentrated proteins resulted in condensates with partitioning and dynamics values of individual components in quantitative agreement with cellular P bodies (39). Reconstitutions using single components, or more generally using arbitrarily-reduced complexity, often still form condensates in vitro , but these condensates are distinct from cellular condensates in terms of their composition and/or material properties (62). While we have not yet assayed the function of our in vitro P bodies, we suggest that this level of reconstitution – including three enzymes and many regulators of these enzymes – will allow for the examination of multiple relevant biochemical activities, and the interplay between these activities (see Discussion).…”
Section: Discussionmentioning
confidence: 99%
“…Our method can also be extended to describe more complex behavior of biomolecular condensates, including response to external cues [19,47], active regulation [48][49][50], and noise buffering [51,52]. Ultimately, our predictions could be tested using engineered condensates [53] and quantitative reconstitution [33]. Beside these concrete applications for biomolecular condensates, our method might also answer more fundamental questions about evolving systems: How can a cell exhibit robust functions while its proteins evolve [54][55][56]?…”
Section: Discussionmentioning
confidence: 99%
“…This showed that the number of coexisting phases typically depends on the overall composition of the system, but it is unclear how this phase count depends on the component count and the specific interaction matrix. Answering this question is critical, since typical biological condensates consist of many components [28,[31][32][33] and the scaffold-client picture [34], where a single scaffold component dominates the phase behavior, might not always apply. State-of-the art numerical techniques can simulate mixtures of up to 16 components [35,36], but these techniques are often too costly to truly explore the space of possible interactions.…”
mentioning
confidence: 99%